PREPARATION AND CHARACTERISATION OF ZnO THIN FILMS DEPOSITED BY RF SPUTTERING METHOD (FUDMA JOURNAL OF SCIENCES, 2024)
Zinc oxide (ZnO) thin films deposited on corning glass substrates at 100ºC substrate temperature by radio frequency deposition were annealed the open air and icrowave oven at 150ºC. The influence of open-air annealing (OAA) and microwave annealing (MWA) were studied. The results obtained showed that MWA annealing can improve not only the crystal but also the optical properties of the ZnO thin films. A high transmittance is obtained in all the annealed samples (S1, S2, S4 and S5) demonstrating >90% at 650 nm wavelength. Reflectance in all the samples was < 29% with a minimum standing at 23.78% as recorded for sample S5. The band gap for the annealed samples (S1, S2, S4 and S5) was determined at 3.26 eV, 3.32 eV, 3.29 eV and 3.34 eV respectively. Absorption coefficient stood at 0.0225 cm-1, 0.0179 cm-1, 0.0180 cm-1, 0.0186 cm-1 and 0.0181 cm-1 for the as-deposited sample and the respectively. The optical and structural properties analysis showed that OAA and MWA annealing at suitable temperatures considered can significantly improve some properties of the ZnO thin films making the films suitable for applications in optoelectronics and photovoltaics.
Keywords: Zinc oxide; Microwave annealing (MWA); open-air annealing (OAA); RF Sputtering; XRD